(untitled) (The Strategic Review for Southern Africa, 2020)
Reconciliation has become an integral part of the post-conflict peacebuilding process, and has come to be seen as an integral part of sustaining peace and security, particularly at the local level. The tension between a state security and human security approach to peacebuilding is particularly evident in national reconciliation and transitional justice processes. There is a continued emphasis on high-level reconciliation processes and the reconciliation of elite actors over processes that facilitate reconciliation at the community level. This article explores this in the case of Zimbabwe, where the emphasis is on a state-based approach to resolving conflict, which fails to take into account or address the needs and issues that affect local communities. Drawing from fieldwork undertaken in Matabeleland in April, 2014, this article describes what community members identify as their central needs when it comes to reconciliation, within the context of the state-driven processes that have been implemented to date.